Campbell and the Colleges - Gresham, Perry Epler (Reed Lectures, 1973)
Based on the Reed Lectures from 1971, Gresham, the twelfth president of Bethany College, explores how the school's founder Alexander Campbell articulated his philosophy of education. He then, demonstrates how leaders affiliated with Disciples of Christ went on to found other institutions of higher education. This study shows the variety of entrepreneurial institutions begun within the Stone-Campbell tradition and the challenges of survival that schools faced even in the early 1970s. Chapters include: ▪ Campbell on Education ▪ Campbell's Bethany ▪ Subsequent Colleges and the Campbell Heritage ▪ The Present Predicament of the Colleges